Eye–Hand Coordination during Learning of a Novel Visuomotor Task - Sailer, Uta (J Neurosci, 2005)
We investigated how gaze behavior and eye–hand coordination change when subjects learned a challenging visuomotor task that required acquisition of a novel mapping between bimanual actions and their visual sensory consequences. By applying isometric forces and torques to a rigid tool held freely between the two hands, subjects learned to control a cursor on a computer screen to hit successively displayed targets as quickly as possible. The learning occurred in stages that could be distinguished by changes in performance (target–hit rate) as well as by gaze behavior and eye–hand coordination. In a first exploratory stage, the hit rate was consistently low, the cursor position varied widely, and gaze typically pursued the cursor. In a second skill acquisition stage, the hit rate improved rapidly, and gaze fixations began to mark predictively desired cursor positions, indicating that subjects started to program spatially congruent eye and hand motor commands. In a third skill refinement stage, performance continued to improve gradually, and gaze shifted directly toward the target. We suggest that during the exploratory stage, the learner attempts to establish basic mapping rules between manual actions and eye-movement commands. In this process, subjects may establish correlations between hand motor commands and their visual sensory consequences, primarily in fovea-anchored, gaze-centered coordinates, and correlations between recent hand motor commands and eye motor commands. The established mapping rules are then implemented and refined in the skill acquisition and refinement stages.